Strategi Pengembangan UMKM Desa Kragilan menuju Wirausahawan Desa yang Berbasis Digitalisasi dalam Program KKN-MAS - Mufti Mubarak Asmar, Andi; Bonewati, Andi; Andi Trisnowali MS; Arifin, Sartika; Zainal Arifin, Muhammad (Rengganis Jurnal Pengabdian Masyarakat, 2024)
This devotion explores how entrepreneurs can develop their businesses within the realm of the Muhammadiyah Aisyiyah Community Service Programme (KKN-MAs). The Muhammadiyah Aisyiyah Community Service Programme (KKN-MAs) is an important breakthrough in the context of helping to solve problems faced by a village or community environment, which emphasises the empowerment of rural communities, social care, and multiplying learning experiences and expanding relationships. In addition, the purpose of the KKN-MAs programme is to train students before entering the workforce, and also to provide a platform for students to explore the implementation of their knowledge for approximately six semesters. This research used a mixed-methods approach, involving document analysis, interviews, and case studies to investigate the strategies used by entrepreneurs to grow their businesses, which were concretely applied in the context of MSME digitalisation in the KKN-MAs programme. The findings of this community service identified challenges and potential improvements in developing MSMEs, particularly in Kragilan Village. The results of this study contribute to MSME entrepreneurs' understanding of digitalisation